NOVEL BUMI MANUSIA KARYA PRAMOEDYA ANANTA TOER KAJIAN SOSIOLOGI SASTRA - Hastuti, Nur (Faculty of Humanities, Diponegoro University, 2018)
â€œBumi Manusiaâ€ is a novel showing the mental turmoil of the characters situated between two cultures, two values, and two understandings. This novel successfully describes not only the cultural revolution in a colonized country but also an objection against the absolute supremacy of cultural and social value. The material object of this research is a novel entitled â€œBumi Manusiaâ€ written by Pramudya Ananta Toer, with the formal object, that is, the description of social relationship between the Java and the European society, or otherwise between the bourgeois and the proletarian. This research adopts the literature sociology approach as the perspective study. Literature sociology is an approach focusing on the relationship between literature works and social values in the life of the author and readers. The discussion and result of this research are conflict, confrontation, as well as social relationship between the bourgeois and the proletarian. The European thought that they were in the highest level, because of being educated compared to the Javanese, so the Javanese had to believe whatever they said. On the other side, there were some natives of European descent who behaved humbly and treated the native in a good way although they had European blood and they were rich, one of them is Annelies. Minke, a blue-blooded native of Java, was able to get out of her â€˜Javanese caterpillarâ€™ to be an independent and free human. She, even, split her â€˜European soulâ€™ which she got from school, which became the symbol and â€˜qiblahâ€™ of knowledge and civilization at that time.